2010
DOI: 10.1073/pnas.1004432107
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction or catalase inactivation extends yeast chronological lifespan by inducing H 2 O 2 and superoxide dismutase activity

Abstract: The free radical theory of aging posits oxidative damage to macromolecules as a primary determinant of lifespan. Recent studies challenge this theory by demonstrating that in some cases, longevity is enhanced by inactivation of oxidative stress defenses or is correlated with increased, rather than decreased reactive oxygen species and oxidative damage. Here we show that, in Saccharomyces cerevisiae, caloric restriction or inactivation of catalases extends chronological lifespan by inducing elevated levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
230
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(258 citation statements)
references
References 30 publications
26
230
0
2
Order By: Relevance
“…These findings suggest that increased mitochondrial superoxide generation acts as a signal in young mutant animals to trigger changes of gene expression that prevent or attenuate the effects of subsequent aging. These findings were consistent with, and significantly extended, earlier studies in yeast [45] and in worms [46] that had suggested that an increase in ROS from mitochondria might be important in triggering the lifespan extension produced by glucose restriction.…”
Section: Ros Signaling Affects Aging and Lifespansupporting
confidence: 92%
“…These findings suggest that increased mitochondrial superoxide generation acts as a signal in young mutant animals to trigger changes of gene expression that prevent or attenuate the effects of subsequent aging. These findings were consistent with, and significantly extended, earlier studies in yeast [45] and in worms [46] that had suggested that an increase in ROS from mitochondria might be important in triggering the lifespan extension produced by glucose restriction.…”
Section: Ros Signaling Affects Aging and Lifespansupporting
confidence: 92%
“…A recent study has also shown CR elevates H 2 O 2 levels in an early stationary phase, and induces SOD activity to help extending CLS [20,47]. Our results showing H 2 O 2 can mimic CR to extend yeast CLS provides supports to such putative mechanisms.…”
Section: Discussionsupporting
confidence: 61%
“…While ME occurs only in the early CR phase (short-term or acute CR), PME maintains in the late CR phase (life-long or chronic CR). Because CR can trigger hydrogen peroxide (H 2 O 2 ) burst and induce superoxide dismutase (SOD) overexpression [20], and NO can reversibly bind to the heme moiety of COX [21], we assume CR-triggered NO may interact with COX to result in H 2 O 2 generation and SOD induction through mitochondrial uncoupling, thereby scavenging reactive oxygen species (ROS), attenuating oxidative stress, guiding metabolic conversion, and eventually extending lifespan.…”
mentioning
confidence: 99%
“…Notably, these genes could not be predicted by neither gene expression analysis alone nor by the commonly used prediction methods. Providing mechanistic explanations to their workings, we further show that in accordance with the model's predictions, the knockout of the two lifespan-extending genes results in a significant elevation in ROS levels, potentially suggesting a hormetic mechanism, as previously shown by Masquita et al 48 for H 2 O 2 . Of note, knockout of ADH2 was previously found to extend yeast CLS by driving metabolism away from acetic-acid production 49 , similar to the mechanism suggested by our flux analysis (Fig.…”
Section: Discussionsupporting
confidence: 53%